Implementation of Industrial IoT Integration Using Node-RED and PLC on Cascade Control Level and Flow Plant - Nur Wisma Nugraha; Fitria Suryatini; Noval Lilansa; Farhan Ali Madani Farhan (Jurnal Penelitian Pendidikan IPA, 2025)
Accurate control of liquid level and flow is essential in industrial processes to ensure efficiency and product quality. Conventional single PID control methods often suffer from steady-state errors and slow response times due to the dynamic interaction between level and flow. This research develops a cascade control system using a PLC integrated with a Node-RED based Industrial Internet of Things (IIoT) platform to overcome these limitations. The cascade control system applies two control loops, the outer loop for level control and the inner loop for flow control, with PID parameters optimized through trial-and-error method. IIoT integration enables real-time monitoring, remote control, and data logging through an interactive dashboard. Experimental results show the system is able to achieve stability with steady-state error reduced to ± 0.5 cm, faster settling time and rise time, and better disturbance resistance. Very low communication delays support real-time operation. The system offers a practical and effective solution for precise liquid level and flow control, aligned with the demands of Industry 4.0 and can be a model for educational and industrial applications.